12 Feb 2019
SOAL-SOAL ALJABAR & PEMBAHASANNYA
Diposting oleh YULIA FRINA ANNUR | di Februari 12, 2019 |1. =(6x^2+5x-6)/(2x^2-3x-9)
=((3x-2)(2x+3))/((2x+3)(x-3))
=(3x-2)/(x-3)
2. =3/(x+y)-5/(x^2-y^2 )
=3/(x+y)-5/((x-y)(x+y))
=(3(x-y)-5)/((x+y)(x+y))
=(3x-3y-5)/(x^(2-) y^2 )
3. =(a-2)/(6a^2-5a-6)+(2a+1)/(9a^2-4)
=(a-2)/((3a+2)(2a-3))+(2a+1)/((3a+2)(3a-2)
=(a-2(3a-2)+2a+1(2a-3))/((3a+2)(3a+2))
4. =((3a^2-2a-6a+4)+(4a^2-6a+2a-3))/((3a+2)(3a+2))
=((3a^2-8a+4)+(4a^2-4a-3))/(9a^2+6a+6a+4)
=(7a^2-12a+1)/(9a^2+12a+4)
5. =(16/49) (_^(3/))2
=(4^2/7^2 ) (_^(3/))2
=(4^2/7^2 ) (_^(3/))2
=4^3/7^3
=64/343
6. =-(1/64) (_^(5/))6
=-(2^(-6))(_^(5/))6
=-(2^(-1) )^5
=-(2^(-5) )
=-(1/32)
7. =x-2y(-32)(_^(4/))5
=(-2^5)(_^(4/))5
=(-2)^4
=16
8. =5a+3a-6a=2a
9. =(13a^2-b^2 )+(-4a^2+3b^2 )-(6a^2-5b^2)
=(9a^2+2b^2 )-(6a^2-5b^2)
=3a^2+7b^2
10. =(2ab-3bc)-[5-(4ab-2bc)]
=2ab-3bc-5+4ab+2bc
=6ab-bc-5
11. =(2x+5y-4)3x
=(2x.3x)+(5y.3x)-(-4.3x)
=6x^2+15xy+12x
12. =a^3+b^3
=(a+b)(a^2-2ab+b^2)
13. =5x-10y
=5(x-2y)
14. =x^2+4x+4
=(x+2)(x+2)
=(x+2)^2
15. =x^2-3x-4
=(x-4)(x+1)
16. =8/(12x+20)
=8/(4(3x+5))
=2/(3x+5)
17. =(9x^2)/(12xy-15xz)
=(3x.3x)/(3x(4y-5z))
=3x/((4y-5z))
18. =(2a+b)/10+(a-6b)/15
=(6a+3b+2a-12b)/25
=(8a-9b)/25
frinaaa.blogspot.com
Langganan:
Posting Komentar (Atom)
0 komentar:
Posting Komentar